Laser Scanner al servizio del Patrimonio Monumentale Ecclesiastico italiano - CAM2, CAM2 (Archeomatica, 2014)
The Centre for Researc h Master in Arc hitecture, Sacr ed Art and Liturgy has spent really excellent results with a CAM2 Laser ScannerFocus3D to detect the architecture of the magnificent Cathedral of Sessa Aurunca.